2011
DOI: 10.2147/vhrm.s25798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking cessation on central blood pressure and arterial stiffness

Abstract: Purpose:Smoking affects arterial stiffness, thus causing an elevation in central blood pressure (CBP). The present study was designed to examine whether smoking cessation treatment improved CBP and arterial stiffness.Patients and methods:We conducted an observational study of 70 patients receiving smoking cessation treatment. Before and 60 weeks after the start of a 12-week varenicline treatment, we measured brachial blood pressure, CBP, brachial-ankle pulse wave velocity (baPWV), normalized radial augmentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 28 publications
1
24
1
2
Order By: Relevance
“…Although the mechanisms are not still clear, endothelial dysfunction and oxidative stress may play important roles in the relationship between AI and cigarette smoking. [28,29] Further, the present study indicated a clear dose–response relationship between AI and smoking status in males, in which AI might be increased as a marker of smoking-specific oxidative stress. [29] Although AI levels in former smokers (81.3%) were slightly elevated than those in nonsmokers (81.2%) in this study, former smokers showed an almost normal range of AI levels.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Although the mechanisms are not still clear, endothelial dysfunction and oxidative stress may play important roles in the relationship between AI and cigarette smoking. [28,29] Further, the present study indicated a clear dose–response relationship between AI and smoking status in males, in which AI might be increased as a marker of smoking-specific oxidative stress. [29] Although AI levels in former smokers (81.3%) were slightly elevated than those in nonsmokers (81.2%) in this study, former smokers showed an almost normal range of AI levels.…”
Section: Discussionsupporting
confidence: 51%
“…[28,29] Further, the present study indicated a clear dose–response relationship between AI and smoking status in males, in which AI might be increased as a marker of smoking-specific oxidative stress. [29] Although AI levels in former smokers (81.3%) were slightly elevated than those in nonsmokers (81.2%) in this study, former smokers showed an almost normal range of AI levels. By contrast, AI levels between light and heavy smokers seemed to be comparable, suggesting that smoking cessation, but not cutting down, may be favorable to the reduction of oxidative stress, as previously reported.…”
Section: Discussionmentioning
confidence: 56%
“…The present study adds to a number of investigations, which have consistently shown a reduction in cfPWV over the short term, following different lifestyle interventions, including not only physical exercise [11][12][13][14][15][16] but also weight loss, smoking cessation and salt intake restriction [17][18][19][20][21][22][23][24][25] (Table 1).…”
mentioning
confidence: 58%
“…Although some studies have reported on the effects of smoking cessation on arterial stiffness, the effects of varenicline on arterial stiffness are unclear. Takami and Saito reported that arterial stiffness parameters significantly decreased in smokers treated with varenicline a year after treatment (33 …”
Section: Discussionmentioning
confidence: 99%